Beneficial effects of mycophenolate mofetil on cardiotoxicity induced by tacrolimus in wistar rats. Issue 4 (February 2017) - Ferjani, Hanen; Timoumi, Rim; Amara, Ines; Abid, Salwa; Achour, Abedellatif; Bacha, Hassen; Boussema-Ayed, Imen
The immunosuppressive drug tacrolimus (TAC) is used clinically to reduce the rejection rate in transplant patients. TAC has contributed to an increased prevalence of cardiovascular disease in patients receiving solid organ transplantation. Mycophenolate mofetil (MMF), a potent inhibitor of de novo purine synthesis, is known to prevent ongoing rejection in combination with TAC. In the present study, we investigated the antioxidant and antigenotoxic effect of MMF on TAC-induced cardiotoxicity in rats. Oral administration of TAC at 2.4, 24, and 60 mg/kg b.w. corresponding, respectively, to 1, 10, and 25% of LD50 for 24 h caused cardiac toxicity in a dose-dependant manner. TAC increased significantly DNA damage level in hearts of treated rats. Furthermore, it increased malondialdehyde (MDA) and protein carbonyl (PC) levels and decreased catalase (CAT) and superoxide dismutase (SOD) activities. The oral administration of MMF at 50 mg/kg b.w. simultaneously with TAC at 60 mg/kg b.w. proved a significant cardiac protection by decreasing DNA damage, MDA, and PC levels, and by increasing the antioxidant activities of CAT and SOD. Thus, our study showed, for the first time, the protective effect of MMF against cardiac toxicity induced by TAC. This protective effect was mediated via an antioxidant process.